Pengembangan Media Pembelajaran Smart Box Materi Teks Narasi pada Siswa SDN 51 Sumarambu Kecamatan telluwanua Kota Palopo - qayyimah; Muhammad Guntur; Nurul Aswar (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
This study aims to develop Smart Box learning media for narrative text material for students of SDN 51 Sumarambu, Telluwanua District, Palopo City. The development model used is 4D (Define, Design, Develop, and Disseminate). This study uses a mixed method approach. Data collection techniques are carried out through observation, interviews, documentation, and questionnaires. The subjects of this study were 21 students of phase B grade IV. The results of the study showed that students liked 3-dimensional media with interesting illustrations and contained explanations of learning materials that explain the concept of narrative text. The design of the Smart Box media was designed in the form of a box measuring 50 cm x 30 cm made of plywood. The development of learning media was validated by three experts, namely media experts gave 75% with a valid category, material experts 81.25% with a very valid category, and language experts 86.11% with a very valid category. Meanwhile, the results of limited trials of the Smart Box learning media by students were 85.71% with a very practical category, and by teachers as much as 77.5% with a practical category. The distribution of Smart Box learning media is carried out through training for teachers/initial users.